AKSES INFORMASI PASAR, MODAL, DAN TEKNOLOGI OLEH PETANI DI DAERAH PERKOTAAN - Dewi, Ida Ayu Listia (Program Studi Agribisnis Fakultas Pertanian Universitas Dwijendra, 2011)
Â Â Â The current condition of Indonesian agriculture shows that the income of those working in agricultural sector is lower than the income of those working in the other sectors.Â Small scale farming, limited capital, being highly dependent on season, employing family members, highly low market, access to loan and technology feature our agriculture.Â Small farmers with their various limitations have caused the agricultural condition in Indonesia to be getting worse.Â One of their limitations is accessibility.Â This will influence the process of making decision as to what commodities should be developed and what technology should be applied.Â This will also indirectly contribute to the farmersâ?? welfare.Â Â Â Â Access to information on transfer of technology, market, capital and other innovations is highly important and needed by farmers to improve their farming enterprises.Â Good access to information will allow the farmers to improve their farming management so that their agribusiness will be better.Â Â Â Â This studi aimed at identifying the degree of accessibility of the farmers at Subak Anggabaya to information on market, capital, and technology.Â The location where the study was conducted was chosen purposively, that is, at Subak Anggabaya, Penatih Village, Denpasar City.Â 30 farmers were used as the respondents.Â the data were obtained using simple random sampling technique.Â It is a descriptive study.Â Â Â Â The results showed that the degree of the accessibility to information on market and capital was still low, that is, 25% and 35%.Â Their accessibility to technological information also showed low condition, that is, 36,9%.Â Meaning that the farmersâ?? ability to obtain information on market, capital, and technology are still needed improving.Â It was expected that those who were in charge of field agricultural extension would be able to give the information needed especially the information on market, capital, and technology.Â It was expected that such information should be equally spread among the farmers.Keywords: access to information on market, access to information on capital, and access to information on technology.Â